La Guadeloupe et ses espaces pénitentiaires : quelles discontinuités de l’ordre en outre-mer ? - Marie Redon; Delphine Grancher (EchoGéo)
In a national context questioning the legal system both downstream (safety obession) and upstream (prison overcrowding) what do overseas specificities say about the order in place there? Guadeloupe is the top-ranked French department in terms of delinquency; 44 homicides of 2013 show a tragic uneasiness in the insular social order. In addition, a severe prison overcrowding is observable in overseas prison centers. Among the institutions where the situation is critical in terms of ratio number of inmates / places, the prison of Baie-Mahault is iconic, like the Basse-Terre one by its antiquated. In an overseas insular space as Guadeloupe, do these sovereign institutions are depending on the metropolitan extraterritoriality or on the surrounding area? This paper’s hypothesis is that the prison spaces are offering a prism for the analisys of the intensity of ties between mainland France and Guadeloupe, and the overseas dependencies beyond. Through the example of Guadeloupe, this text provides an overview on the link between two forms of discontinuities: prison spaces and overseas status. It shows the judicial and penitentiary characteristics of Guadeloupe, the expressions of remoteness from the mainland France and the inclusion of this area in the Caribbean environment. All of it is matter of permanent territorial compromise.